Analisis Prosedur Pemberian Kredit Dan Penagihan Piutang Pada Kantor Cabang PT. BPR Pijer Podi Kekelengen Simpang Selayang - Simamora , Carmenita Natania; Manurung, Amran; Siringoringo, Magdalena J. (CV. ITTC INDONESIA, 2024)
This study aims to analyze the procedures for granting credit and collecting receivables in a company in order to identify the effectiveness and efficiency of the system used. Credit granting is an important aspect in financial management that can affect the company's liquidity and profitability. However, if not managed properly, this can increase the risk of bad debts and have a negative impact on the company's financial health. This study uses a qualitative descriptive method by collecting data through interviews, observations, and documentation. The results of the study indicate that the credit granting procedures in the company analyzed have followed applicable standards, but there are still some weaknesses in the credit assessment process that can lead to the risk of bad debts. On the other hand, receivables collection in the company still faces challenges in terms of timeliness and effectiveness of communication with customers. Thus, it is expected that the company can increase liquidity and reduce the risk of bad debts, which ultimately contributes to the company's financial stability.